Building Sustainable Performance at PT PLN in Synergy With A Conducive Work Environment and Employee Motivation - Muhammad Arofiq; Yenny Maya Dora (IJSM, 2026)
This study aims to analyze the influence of the work environment on employee performance with motivation as a mediating variable at PT PLN (Persero) Disjabar, particularly under the auspices of UP3 Bandung, which is facing increasing customer complaints. The background of the study is based on the gap between PLN's positive macro performance achievements and the operational reality in the customer service unit. The research method uses a quantitative approach with a survey of 95 respondents selected proportionally from three ULPs, namely Cijawura, Kopo, and Ujung Berung. Data were collected through a Likert scale questionnaire and analyzed using path analysis assisted by SPSS, including partial tests, simultaneous tests, and Sobel tests to examine the role of mediation. The results show that the work environment has a significant effect on employee motivation and performance. In addition, motivation is also proven to have a positive effect on performance and acts as a significant mediator in the relationship between the work environment and performance, although the direct influence of the work environment is more dominant. The novelty of this study lies in the finding that improvements in the physical, social, and psychological work environment are the main factors in improving performance, while motivation serves to strengthen and maintain the continuity of its impact. These findings provide practical implications that PLN needs to integrate strategies to improve the work environment with strengthening employee motivation to reduce customer complaints and improve service quality sustainably.